2010
DOI: 10.1177/001979391006300408
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Women Faculty at Public Research Universities: Do Unions Matter?

Abstract: The authors investigate the impact of unionization on the representation of women faculty at public Carnegie Doctoral/Research-Extensive institutions in the United States from 1993-94 through 2004-05. Using institutional-level data from the American Association of University Professors and controlling for important characteristics that influence the gender composition of faculty, the authors find that important differences exist in the proportion of women faculty in total and by rank in unionized versus non-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…May et al . () found that unionised universities outperformed their non‐unionised counterparts in increasing the percentage of women faculty overall and at the ranks of full and associate professor. Our results question the positive effectiveness of unionisation on the percentage of female academic economists at the associate professor rank.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…May et al . () found that unionised universities outperformed their non‐unionised counterparts in increasing the percentage of women faculty overall and at the ranks of full and associate professor. Our results question the positive effectiveness of unionisation on the percentage of female academic economists at the associate professor rank.…”
Section: Resultsmentioning
confidence: 98%
“…About one‐third of US college and university faculty are unionised. According to previous work, unionised institutions may perform better in retaining female faculty because of the provision of clearer tenure and promotion review procedures and also procedures to voice complaints in union contracts (May et al ., ). In addition, unions' effort to address work and family issues including childcare services, elder care programs, flexible work schedules and a range of family leave options may exert a positive effect (Crouter and Booth, ).…”
Section: Research Frameworkmentioning
confidence: 97%
See 1 more Smart Citation
“…Not only were women represented in lower numbers, they were also paid less. Potential reasons for this disparity and unequal representation include women a) spending a greater amount of time in lower ranks and b) being less likely to be promoted (May, Moorhouse, & Bossard, 2010). Additionally, discriminatory attitudes, such as believing women are incapable of being a leader, impeded women's entry into leadership positions as well as limiting the advancement opportunities in such roles (Jakobsh, 2004).…”
Section: Women Leaders In Universitiesmentioning
confidence: 99%
“…Since 1980, the proportion of females enrolled in higher education has exceeded the proportion of males (National Center for Education Statistics 2006). Along with an increase in females' educational attainment, including graduate education, an increased number of females have chosen academia as a career path (May, Moorhouse, and Bossard 2010).…”
Section: Female Faculty In the Us Academy Of Higher Educationmentioning
confidence: 99%